A highly transparent polymer coating on the glass with broadband antireflection, antifogging and antifouling properties. (5th April 2019) - Feng, Chenchen; Gou, Tong; Li, Juan; Cai, Yelun; He, Pan; Huang, Jingbo; Wen, Yihao; Ma, Yingjun; Zhang, Zhiying
Abstract: Transparent coatings with the multiple functions of antireflection, antifogging and antifouling can simultaneously solve the three main issues of reflection, fogging and fouling, which can dramatically improve the light efficiency and utilization convenience of optical elements, such as glass. Here, we report that, the multifunctional bionic polymer moth-eye coating can be fabricated on the glass surface by a facile and low-cost method of template-assisted prepolymer curing. The polymer moth-eye arrays can firmly adhere to the glass substrate due to the bonding agent 3-aminopropyl triethoxy silane, which can react with the hydroxy groups of the glass surface and the copolymer, respectively. Due to the high surface energy of the polymer coating, it shows superhydrophilic property and exhibits high average transmittance after fogging for 0 min (98.9%) and 10 min (96.9%) in visible the wavelength range (380–800 nm). It also exhibits ideal repellent to contamination, which still can maintain high transparency (90%) after pulling out from the exemplified graphite powder.